Effectiveness of Electronic Medical Records Implementation in Outpatient Services: A Qualitative Study at Dr. TC Hillers Hospital, Maumere - Marten Preskapu Wela; Agus Syawal Yudhistira; Bernadetha Yustina Nona Ririn; Stefanus Rua (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Electronic Medical Records (EMR) are a key component in the digitalization of healthcare services and are mandated by Minister of Health Regulation No. 24 of 2022. How-ever, their implementation still faces infrastructure and human resource readiness challenges, particularly in outpatient units. This study aims to evaluate the effectiveness of EMR Clinical use at Dr. TC Hillers Regional General Hospital, Maumere. Therefore, Qualitative research was conducted through in-depth interviews and observations of the outpatient service flow. Six informants were purposively selected, including medical records management, operational staff, and patients. The analysis focused on effectiveness based on tasks and functions, goals and benefits, and service plans and programs. Some of the results obtained were: RME increased internal efficiency, particularly in re-ducing paper use, accelerating data access, and simplifying administration. Staff assessed the system as simplifying their work. However, effectiveness was hampered by an unstable net-work and limited formal training. From a patient perspective, the service process, particularly registration, was considered slower due to technical glitches. However, overall, the implemen-tation of RME was considered quite effective, although not optimal for end users. Therefore, network improvements, strengthening human resource training, and patient education are need-ed to maximize the system's effectiveness.